High national and sub-national coverage of iodised salt in India: evidence from the first National Iodine and Salt Intake Survey (NISI) 2014–2015. Issue 16 (10th September 2018) - Pandav, Chandrakant S; Yadav, Kapil; Salve, Harshal R; Kumar, Rakesh; Goel, Akhil D; Chakrabarty, Arijit
Abstract: Objective: The National Iodine and Salt Intake Survey (NISI) 2014–2015 was undertaken to estimate household iodised salt coverage at national and sub-national levels in India. Design: Cross-sectional survey with multistage stratified random sampling. Setting: India was divided into six geographic zones (South, West, Central, North, East and North-East) and each zone was further stratified into rural and urban areas to yield twelve distinct survey strata. Subjects: The target respondent from each household was selected as per predefined priority; wife of the household head, followed by women of reproductive age, followed by any adult available during the visit. Results: Households ( n 5717) were surveyed and salt samples ( n 5682) were analysed. Household coverage of iodised salt (iodine≥5 ppm) was 91·7 (95 % CI 91·0, 92·7) %. Adequately iodised salt (iodine≥15 ppm) was consumed in 77·5 (95 % CI 76·4, 78·6) % of households. Significant differences in coverage were seen across six geographic regions, with North and North-East zones on the verge of achieving the universal salt iodisation target of >90 % coverage. Coverage of households with adequately iodised salt (adjusted OR; 95 % CI) was significantly less in rural households (0·55; 0·47, 0·64), lower/backward castes (0·84; 0·72, 0·98), deprived households (0·72; 0·61, 0·85) as assessed by multidimensional poverty index, households with non-diverse diet (0·73; 0·62, 0·86) and households using non-packaged salt (0·48; 0·39, 0·59) and non-refined salt (0·17; 0·15, 0·20). Conclusions: India is within striking reach of achieving universal salt iodisation. However, significant differentials by rural/urban, zonal and socio-economic indicators exist, warranting accelerated efforts and targeted interventions for high-risk groups.